Investigating Future Educators Training to Teach English in Ecuador: An Examination of one University's Program - Mayra C. Daniel; Ximena Burgin (Athens Institute for Education and Research, 2019)
Education in Ecuador is undergoing a process of change led and supported by the country's government leaders. In this study, researchers use a wide-angle lens informed by governmental mandates to investigate English language teaching. They examine how English language teachers are trained for the K-12 Ecuadorian context within one university's region. The 40 participants, students completing a school-based internship during the last year of their training to become teachers, represent a sample of Ecuador's cultural and linguistic diversity. This work is informed by findings from a previous study, consisting of observations and interviews of practicing teachers (Burgin & Daniel, 2017). Using mixed methods, this research includes surveys and focus groups conducted before and after delivery of instructional workshops centered on topics related to English language instruction and teacher training. Findings indicate mixed-results from pre to post for teachers' cultural beliefs; however, positive change was found regarding participants' attitudes toward multicultural students. Data revealed that teachers require more support to deliver instruction that is appropriate for monolingual and multilingual student populations.